Ativismo jurídico e luta de classes: o protagonismo da política na arena jurídica - Machado Filho, Paulo Celso (2021)
This bibliographical theoretical research deals with the understanding of legal activism and class struggle. The research hypothesis is to logically reveal how politics stands out in the legal field. To this end, the works of Evguiéni B. Pachukanis (2017), Nicos Poulantzas (1977) and Louis Althusser (1970 and 1999) were used as a reference in the investigation of the problem, linked to the theories of habitus, field and cultural capital of Pierre Bourdieu. Based on these definitions and theories, it is understood that legal activism disrespects the separation of state powers, however, that needs to be observed with the scientificity of historical materialism in its current temporality and spatiality, because only in this way is it seen as the social representation that it is. Legal activism is characterized as a powerful instrument that is legitimized through the discourses founded on capitalism and placed as precepts linked to the slowness of laws, their disconnected accompaniment to the will of the people. It is also associated with personality, freedom, equality and fraternity and, with that, it creates the Law of social relations, especially of trade relations, which shows the dominance of the ideological in the legal-political region, trained to hide its ideological and primordial political bias. The greatest expected contribution of the study is to create a controversy over the ―made‖ responses in critical social moments, but that do not question the organicity, the organizational bulge of the law. The discourse is flawed as it remains on the surface of the judicial governance of society and, therefore, it still needs to drop its mask of exemption to demonstrate the true face of law in the contemporary: that of a State instrument in the service of capital.